(untitled) (Journal of Astronomy & Earth Sciences Education, 2015)
For nearly four years, NASA’s Kepler space telescope searched for planets like Earth around more than 150,000 stars similar to the Sun. In 2008 with in-kind support from several technology companies, our non-profit organization established the Pale Blue Dot Project, an adopt-a-star program that supports scientific research on the stars observed by the Kepler mission. To help other astronomy educators conduct successful fundraising efforts, I describe how this innovative crowdfunding program successfully engaged the public over the past seven years to help support an international team in an era of economic austerity.